Evaluation and management of blepharoptosis - Cohen, Adam J.; Weinberg, David A. (Springer, 2011)
This comprehensive and detailed text deals with the diagnosis and surgery of blepharoptosis, and will benefit any practicing physician, fellow or resident who deals with blepharoptosis.